Respuesta :
Answer:
x = -2
Step-by-step explanation:
12 - 2x = 26
-2x = 14
x = 14/-7
x = -2
Answer:
Rearrange terms..
_____________________
12-2x=26
-2x +12=26
Step-by-step explanation:
12-2x=26
We simplify the equation to the form, which is simple to understand
12-2x=26
We move all terms containing x to the left and all other terms to the right.
-2x=+26-12
We simplify left and right side of the equation.
-2x=+14
We divide both sides of the equation by -2 to get x.
x=-7
![Ver imagen Karling](https://us-static.z-dn.net/files/d07/6400a0231b9bb79d037086ffda2e453d.png)